PENGEMBANGAN MULTIMEDIA INTERAKTIF ‘JELAJAH BUDAYA BERSAMA RAJO’ BERBASIS ARTICULATE STORYLINE 3 PADA PELAJARAN PENDIDIKAN PANCASILA KELAS IV SD - Zuardi; Amanda Berlia Bersky (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Education in the 5.0 digital era requires innovative and interactive learning in line with the demands of the 21st century. To realise this, interactive IT-based media centred on students is needed. However, in elementary schools, the use of interactive media is still limited to simple videos or digital quizzes. However, professional software like Articulate Storyline 3 is capable of integrating video, audio, and images to create more engaging and meaningful learning experiences. This research aims to develop interactive multimedia "Exploring Culture with Rajo" based on Articulate Storyline 3 for fourth-grade elementary school students. The research uses the research and development (R&D) method with the ADDIE model, which includes analysis, design, development, implementation, and evaluation. Validation is conducted by experts in content, media, and language. Practicality is assessed through teacher and student questionnaires, while effectiveness is measured using pre-tests and post-tests. Field trials were conducted at SDN 01 Benteng Pasar Atas as the experimental class, SDN 03 Pakan Kurai as the experimental class, and SDN 08 Tarok Dipo as the control class with fourth-grade students. The research results showed material validation of 100%, language 95%, and media 99% (very valid). The practicality according to teachers reached 99% in the trial class and 97% in the experimental class, while students rated it 90% and 94%. The effectiveness of the media with an N-Gain of 76% in the trial class, 83% in the experimental class, and 67% in the control class. It is concluded that this media is valid, practical, and effective for Pancasila Education learning in the fourth grade of elementary school.